Micro mobility scheme in NEMO to support seamless handoff - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Hasan, Mohammad Kamrul; Khalifa, Othman Omran; Saeed, Rashid Abdelhaleem (IEEE, 2012)
With the aim of supporting mobile network, a management mechanism of Network Mobility Basic Support Protocol (NEMO BSP) was standardized by Information Engineering Task Force (IETF) which inherits all the advantages from MIPv6. However, the NEMO BSP is inadequate to support an uninterrupted Internet connection for the MR in NEMO environment. With the aim of providing seamless Internet connectivity, one of the most important concerns during handoff in NEMO networks is to reduce handoff delay with reducing packet loss. To address this limitation, this paper proposes a Micro Mobility scheme in NEMO network that supports fast handoff and hides network mobility by integrating the Improved FHMIPv6 (host based mobility protocol) with NEMO environment. Additionally, analytical results are also compared with the standard NEMO BSP. The numerical results show that the proposed scheme capable to reduce the signaling cost during handoff.